Mitigating the mental health consequences of mass shootings: An in-silico experiment. (September 2022) - Abdalla, Salma M.; Cohen, Gregory H.; Tamrakar, Shailesh; Sampson, Laura; Moreland, Angela; Kilpatrick, Dean G.; Galea, Sandro
Summary: Background: There is emerging evidence that mass shootings are associated with adverse mental health outcomes at the community level. Data from other mass-traumatic events examined the effectiveness of usual care (UC), (i.e., psychological first aid approaches without triage), and stepped care (SC) approaches, with triage, in reducing the burden of post-traumatic stress disorder (PTSD) in a community. Methods: We built an agent-based model of 118, 000 people that was demographically comparable to the population of Parkland and Coral Springs, Florida, US. We parametrized the model with data from other traumatic events. Using simulations, we then estimated the community prevalence of PTSD one month following the Stoneman Douglas High School (Florida, US) shooting and reported the potential reach, effectiveness, and cost effectiveness of different what-if treatment scenarios (SC or UC) over a two-year period. Findings: One month following the mass shooting, PTSD prevalence in the community was 11.3% (95% CI: 11.1–11.5%). The reach of SC was 3461 (95% CI: 3573–3736) per 10, 000 and the reach of UC was 2457 (95% CI: 2401–2510) per 10, 000. SC was superior to UC in reducing PTSD prevalence, yielding, after two years, a risk difference of −0.044 (95% CI, −0.046 to −0.042) and a risk ratio of 0.452 (95% CI, 0.437–0.468). SC was also superior to UC in reducing the persistence of PTSD, yielding, after two years, a risk difference of −0.39 (95% CI, −0.401 to −0.379) and a risk ratio of 0.452 (95% CI, 0.439–0.465). The incremental cost-effectiveness of SC compared to UC was 2718.49 per DALYs saved, and 0.47 per PTSD-free day. Interpretation: This simulation demonstrated the potential benefits of different community-level approaches in mitigating the burden of PTSD following a mass shooting. These results warrant further research on community-based interventions to mitigate the mental health consequences of mass shootings. Funding: None.